Modification of Natural Zeolite as a Catalystfor Steam Reforming of Toluene - Joko Waluyo; Tobias Richards; IGBN Makertihartha; Herri Susanto (ASEAN Journal of Chemical Engineering, 2019)
A catalyst for tar cracking has been prepared successfully from natural zeolites using ion exchange with NH4NO3, and acid leaching with HNO3 solution for removing impurities and increasing pore volume. The activity of the modified zeolite was tested using toluene as a tar model compound. Tar conversion of about 54% was achieved in catalytic steam reforming at a temperature of 750C using 2 gram of catalyst and the gas hourly space velocity about 5040 h-1.